Modeling soil water dynamics to optimize blueberry irrigation in sandy soils - Tucker, Stewart; Yazdanpanah, Najme; Rai, Abraham; Weide, Josh Vander; Dong, Younsuk (Frontiers in Agronomy, 2025)
IntroductionDrip irrigation is widely used by growers to improve application efficiency in high-value crops such as blueberry, where efficient water management is critical. Optimizing soil moisture conditions in blueberry production systems through irrigation system design is of particular importance, as blueberries are typically grown in sandy soils and have a shallow root system. In addition, climate variability in blueberry production regions has complicated irrigation management. The objective of this work was to optimize drip irrigation system design and management practice using the HYDRUS 2D model.MethodsField soil moisture and environmental conditions were monitored using a Sentek Drill & Drop soil moisture sensor system installed at nine depths within the root zone during 2024 growing season in Michigan. The collected field data were used to calibrate The HYDRUS 2D model to simulate soil water distribution under drip irrigation. During calibration, the standard statistical indicators used were Nash–Sutcliffe efficiency (NSE), index of agreement (IA), and root mean square error (RMSE), with values of >0.93, >0.98, and <0.03 cm3/cm3, respectively. Four numerical experiments were conducted in HYDRUS 2D to optimize drip irrigation system management. These experiments included evaluating the impact of 1) irrigation application system (single vs. double drip lines), 2) emitter spacing (15-, 30-, 45-, 60-cm), 3) irrigation duration (1-, 0.5-, 0.25- hour), and 4) emitter flow rate (0.98 L/h, 1.89 L/h).ResultsA single drip line, emitter spacing of 45 or 60 cm, a 0.5-hour irrigation duration, and a flow rate of 1.89 L/h optimized irrigation application efficiency and minimized the risk of leaching water below the root zone. In addition, result indicated that in both single and double drip line systems, higher emitter flow rates enhanced soil moisture availability within the root zone. However, longer irrigation durations, such as 1 hour significantly increased the risk of water percolating beyond the effective root depth, particularly in sandy soils. Future research will evaluate alternative modeling approaches and validate the methodology across diverse soil and climate conditions to enhance robustness.DiscussionOverall, the results indicate that the HYDRUS-2D model is a reliable and effective tool for optimizing the design and management of drip irrigation systems in blueberry production. By simulating the dynamic movement of water within the root zone, the model helps identify irrigation conditions that optimize water use efficiency while reducing the risk of water leaching beyond the effective root depth.